Parameters affecting protection coordination of high voltage distribution network with distributed energy resources - Ishan Desai; Nilesh Chothani; Paul Jacob (Institute of Advanced Engineering and Science, 2026)
Distributed energy resources (DERs) have become favorable sources of power against conventional power sources at distribution level because of their advantages like reduction in power loss and voltage drop, and environment friendliness. Integrating of DERs into high voltage distribution networks (HVDNs) introduces significant challenges to protection relay coordination because of their dynamic operational characteristics. This comprehensive study investigates key parameters influencing effective protection relay coordination in distribution networks (DNs), including fault current variability, DER penetration level, network topology, and relay settings. Through comprehensive simulation conducted on modified IEEE 4-bus HVDN with variable DER configurations through PSCAD/EMTDC 4.5 software, the research analysis evaluates the impact of these parameters on protection reliability and speed. Results indicate that high DER penetration leads to fault current increment by 10-20%, grid current contribution reduction by 10-15% as well as relay current setting alterations approximately by 30-40% which necessitates adaptive protection schemes. Network topology and relay coordination strategy significantly affect fault detection and isolation process. The finding provides understanding of parameters affecting protection coordination which helps in its optimization and having reliable and secure operation of DN.